The Association of Health Literacy with High-Quality Home Blood Pressure Monitoring for Hypertensive Patients in Outpatient Settings - Sau Nga Fu; Man Chi Dao; Carlos King Ho Wong; Bernard Man Yung Cheung (International Journal of Hypertension)
Worldwide hypertension (HT) guidelines recommend use of home blood pressure monitoring (HBPM) in patients with persistent suboptimal blood pressure (BP) readings. It is not clear how patients with limited health literacy could perform HBPM to assist BP control. This study aimed at finding the association between HBPM and patients from lower socioeconomic classes, particularly on the effect of health literacy or educational level. Three electronic databases (MEDLINE, EMBASE, and PubMed) were searched for primary studies with keywords including educational level, health literacy, numeracy, home blood pressure monitoring, accuracy, and quality. The PRISMA guideline was followed. The quality of the literature was assessed by the Cochrane tool and modified Newcastle-Ottawa Scale. Nineteen interventional studies and 29 cross-sectional studies were included. Different populations used different cutoffs to report patients’ educational level, whereas health literacy was rarely measured. Three studies used psychometric validated tools to assess health literacy. The quality of HBPM could be assessed by the completion of the procedures’ checklist or the number of HBPM readings recorded. The association between subjects’ health literacy or educational level and the quality of HBPM was variable. The interventional studies showed that increasing professional-patient contact time could improve patients’ knowledge, efficacy, and quality of HBPM. Conclusion. Patients’ educational level and literacy were not the limiting factors to acquire high-quality HBPM. High-quality HBPM could be achieved by the structured educational intervention. The quality and amount of evidence on this topic are limited. Therefore, further studies are warranted.